The Effect of Exchange Rate, Money Supply, Inflation, and BI-7DRR on Net Asset Value of Sharia Mutual Funds - Sholeha, Ulfatus; Fadhlillah, Penny Rahmah (SAN Scientific, 2023)
This research aims to examine the individual and combined impacts of the Rupiah Exchange Rate (Exchange Rate), Money Supply, Inflation, and BI 7DRR on the Net Asset Value (NAV) of Sharia Mutual Funds. The study employs a quantitative approach using secondary data, with a sample size of 60 NAV data points from Islamic Mutual Funds recorded monthly between January 2016 and December 2020. The Error Correction Model (ECM) Engel-Grange is utilized as the analytical method. The findings indicate that, on a partial basis, the Exchange Rate and BI 7DRR variables do not have a significant influence on the NAV of Sharia Mutual Funds. However, the Money Supply and Inflation variables demonstrate a positive and significant impact on the NAV of these funds. Moreover, when considered together, the Exchange Rate, Money Supply, Inflation, and BI 7DRR variables jointly exhibit a significant effect on the NAV of Sharia Mutual Funds. As a result, it is suggested that the government should create a secure and profitable environment for Sharia mutual funds to foster continuous growth. An evident sign of the expansion of Islamic mutual funds is the increasing number of units offered to investors in the community.